2019
DOI: 10.1021/acs.iecr.8b05525
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Surface Chemistry of Gas-Wetting Nanoparticles and Their Effect on the Liquid Menisci in Porous Media

Abstract: The transformation of the liquid menisci at pore throats is of great importance for mitigating the liquid-blocking effect of condensate reservoirs. Here, we reported a super gas-wetting peanut-like nanoparticle which can facilitate the liquid menisci to transform from concave shape to convex shape by coating a super gas-wetting adsorption with high surface roughness. The morphology and surface chemistry of gas-wetting nanoparticles were investigated by SEM, AFM, and XPS analysis. The mechanism of surface modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The existence of carbon dioxide or methane would be considered as the influential parameter of the flow that is called sorption. Moreover, regarding the previous numerical and analytical modeling of the gas transportation in the porous media of shale layers, Knudsen diffusion mechanism would consider as the dominant mechanism in the gas flow rate of shale matrixes. , Yuan et al (2014) were experimentally evaluated the profound impact of particle size on the gas diffusion and adsorption. Hence, it was concluded that Knudsen and Fickian diffusion were the dominated phenomena on the gas transportation of shale gas layers.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of carbon dioxide or methane would be considered as the influential parameter of the flow that is called sorption. Moreover, regarding the previous numerical and analytical modeling of the gas transportation in the porous media of shale layers, Knudsen diffusion mechanism would consider as the dominant mechanism in the gas flow rate of shale matrixes. , Yuan et al (2014) were experimentally evaluated the profound impact of particle size on the gas diffusion and adsorption. Hence, it was concluded that Knudsen and Fickian diffusion were the dominated phenomena on the gas transportation of shale gas layers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there exists a subpeak at approximately 134.6 eV due to the deposition of the oxidized P (P x O y ) on carbon, , as shown in Figure e. Figure f illustrates that the peaks located at 284.8 and 286.2 eV can be ascribed to the CC bond and −COOH group, which further verified the presence of the carboxyl group on CNT …”
Section: Results and Discussionmentioning
confidence: 53%
“…Figure 5f illustrates that the peaks located at 284.8 and 286.2 eV can be ascribed to the CC bond and −COOH group, which further verified the presence of the carboxyl group on CNT. 39 3.6. TGA Analysis.…”
Section: Resultsmentioning
confidence: 99%
“…With the deepening of oil production in subsurface reservoirs, the rheology of drilling fluid is difficult to be effectively controlled, which can easily cause borehole instability, barite settlement, sticking, and other drilling accidents. , Because of lattice substitution, clay minerals in drilling fluids have negative charges on their surface, which adsorb cations to form diffusion layers. , The increase of sodium ions will significantly increase the number of cations in the diffused electric double layer of clay particles, thus compressing the electric double layer, reducing the thickness of the diffused electric double layer and the ζ-potential on the surface of the particles. , In this case, the electrostatic repulsion of clay particles decreases, the hydration film becomes thinner, and the dispersion of particles decreases, which makes the rheological properties of drilling fluid worse and causes frequent drilling accidents …”
Section: Introductionmentioning
confidence: 99%